L'hegemonie dans Au Pays de Tahar Ben Jelloun - Putri Balqis Mu'izzatul As shofiyyah; Novi Kurniawati (Universitas Negeri Semarang, 2026)
Au Pays is a novel by Tahar Ben Jelloun that depicts the lives of North African immigrants in France, who face a subordinate social position due to the cultural and ideological dominance and values of the majority group. The characters face inequalities, discrimination, and identity conflicts linked to the colonial legacy and postcolonial society. This situation aligns with Antonio Gramsci’s theory that power is exercised not only through coercion but also through consent via social and cultural influence. This study aims to analyze hegemonic mechanisms, their influence on immigrant characters, and forms of counter-hegemony in the novel. It adopts a descriptive qualitative approach grounded in hegemony theory. The data, consisting of narrative passages, dialogues, and descriptions, are collected through close reading and note-taking and analyzed using content analysis. The results show that hegemony is expressed through institutions, education, religion, and social norms, leading immigrants to accept their subordinate position. However, the novel also reveals forms of resistance an identity preservation.